2013
DOI: 10.1039/c2dt31502e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of terephthalate-intercalated NiAl layered double hydroxides with high Al content

Abstract: Terephthalate-intercalated nickel-aluminum layered double hydroxides (LDHs) were prepared by a co-precipitation method, with nominal x values in the general formula Ni((1-x))Al(x)(OH)(2)(C(8)H(4)O(4))(x/2) in the range 0.3-0.8. The materials were characterized by X-ray diffraction, X-ray fluorescence spectroscopy, CHN analysis, thermogravimetric analysis, FTIR spectroscopy, EXAFS at the Ni edge and (27)Al NMR spectroscopy. A combination of XRD, XRF and CHN analysis indicated that crystalline LDHs with true x v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…The char yields of PAI/modified NiAl-LDH NCs at 800°C are in the range of 47-56 (Table 1). The obtained results for LOI values (36)(37)(38)(39)(40), confirmed that all NCs can be classified as the self-extinguishing materials.…”
Section: Thermal Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…The char yields of PAI/modified NiAl-LDH NCs at 800°C are in the range of 47-56 (Table 1). The obtained results for LOI values (36)(37)(38)(39)(40), confirmed that all NCs can be classified as the self-extinguishing materials.…”
Section: Thermal Analysissupporting
confidence: 68%
“…The bands at 600, 570, and 425 cm −1 are due to Ni-O-Al deformation mode and Ni-O and Al-O stretching modes. [39] In the spectrum of the amino acid containing diacid, two characteristic peaks at 1777 and 1711 cm −1 are attributable to the asymmetrical and symmetrical carbonyl of the imide groups, respectively. The bands observed at 1387 and 732 cm −1 corresponding to the presence of the imide heterocyclic ring.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…It has been argued that for x N 1/3, the presence of Me-O-Me linkages would be required and these are unfavorable from the point of view of charge repulsion (Rives, 2006), (Evans & Slade, 2006). However, it has been demonstrated that such Me-O-Me linkages can occur in LDHs containing TA as compensating anion by means of co-precipitation method with pH control (Kooli et al, 1996), (Kukkadapu et al, 1997), (Arias et al, 2013). The interlayer organization and thermal stability of LDHs are influenced both by the layer charge and by the degree of hydration (Maxwell et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Although the most common anion is carbonate, terephthalate (TA) has been widely studied most because of its use as swelling agent, to assist the incorporation of bulkier anions (Drezdzon, 1988), (Vucelic et al, 1995), and also because its relatively rigid nature enables studies on the dynamics of interlayer anions, both by spectroscopic, and computational studies (Greenwell et al, 2010). The synthesis of LDH with high layer charge is desirable for some applications such as catalysis (Arias et al, 2013). LDH containing CO 3 with x N 1/3 is rare in the literature (Kukkadapu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Já a comparação dos HDLs intercalados com ânions dos ácidos tereftálico (TA) e 2-aminotereftálico (ATA) teve como motivação analisar a influência do grupo amino no processo de formação do produto. Por esse motivo, o ânion tereftalato foi também intercalado, embora este ânion já tenha sido muito estudado na literatura como, por exemplo, precursor para preparação de HDLs intercalados (ou "pilarizados") com íons polioxometalatos [5,17,[114][115][116]. O íon TA, quando intercalado, promove um aumento no espaçamento interlamelar que facilita a intercalação de íons volumosos por troca iônica.…”
Section: Conclusões Parciaisunclassified